Frequency Properties Research of Elevator Drive System with Direct Torque Control-Pulse with Modulation - A. S. Koval; A. V. Shvayakov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
In the article problems of frequency properties research for electric drive system with direct torque control and pulse width modulator are described. The mathematical description of elevator is present. Simplified mathematical description of direct torque control - pulse width modulator electric drive system is shown. Transfer functions for torque and speed loops are determined. Logarithmic frequency characteristics are computed. Damping properties of elevator drive system are estimated.